Multicenter, randomized, double-blind, controlled trial of transcutaneous electrical nerve stimulation for pancreatic cancer related pain. Issue 5 (5th February 2021) - He, Lihua; Tan, Keping; Lin, Xianming; Yi, Hui; Wang, Xueliang; Zhang, Jiangsong; Lin, Jietao; Lin, Lizhu
Abstract: Background: Up to 80% of patients with pancreatic cancer experience abdominal and back pain. Although pharmacologic medications provide some relief, many report inadequate analgesia and adverse effects. Transcutaneous electrical nerve stimulation (TENS) is a non-invasive physical modality and had been widely applied for pain relieving, yet no study has investigated the effectiveness of TENS for pain in pancreatic cancer. Methods: Eligible patients were randomly assigned in a 1:1 ratio to TENS group or control group. The primary outcome was percentage change of numerous rating scale (NRS) after treatment. Secondary outcomes included percentage change of analgesic medication consumption and effect on constipation and poor appetite. Results: One hundred seventy-one patients were recruited (84 to control group and 87 to TENS group). NRS in TENS group has been largely decreased 77.9% right after treatment and 27.1% in 2 hours, before applying any analgesic medication, while that in control group was slightly downregulated right after treatment but gave a trend to increase at 1, 2, and 3 hours. When comparing both groups, pain was significantly well controlled without analgesic medication supplement in TENS group at 0 hour (difference in mean percent change in NRS = 50.0 [95% CI, 50–51.4], P < .01) and 3 hours (difference in mean percent change in NRS = 134.0 [95% CI, 130.0–142.7], P < .01) after treatment, and this analgesic effect last to 3 weeks after treatment cycle (difference in mean percent change in NRS = 22.5 [95% CI, 17.6–27.3], P < .01) without increase of analgesic medication consumption. Conclusions: TENS reduces pain without increase analgesic medication consumption in patients with pancreatic cancer pain. It provides an alternative therapy for pain in pancreatic cancer. Clinical Trial Registration: This study was registered at ClinicalTrials.gov, identifier NCT03331055.